2021
DOI: 10.1111/acel.13537
|View full text |Cite
|
Sign up to set email alerts
|

The age factor in optic nerve regeneration: Intrinsic and extrinsic barriers hinder successful recovery in the short‐living killifish

Abstract: As the mammalian central nervous system matures, its regenerative ability decreases, leading to incomplete or non‐recovery from the neurodegenerative diseases and central nervous system insults that we are increasingly facing in our aging world population. Current neuroregenerative research is largely directed toward identifying the molecular and cellular players that underlie central nervous system repair, yet it repeatedly ignores the aging context in which many of these diseases appear. Using an optic nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 133 publications
(186 reference statements)
0
12
0
Order By: Relevance
“…As there are no antibodies available to label killi sh RGCs, we used a retrograde tracing to e ciently and truthfully label retinal ganglion cells (RGCs) (Vanhunsel et al 2022). Brie y, sh were anaesthetized as described above and positioned on their side under a stereomicroscope.…”
Section: Retrograde Biocytin Tracingmentioning
confidence: 99%
“…As there are no antibodies available to label killi sh RGCs, we used a retrograde tracing to e ciently and truthfully label retinal ganglion cells (RGCs) (Vanhunsel et al 2022). Brie y, sh were anaesthetized as described above and positioned on their side under a stereomicroscope.…”
Section: Retrograde Biocytin Tracingmentioning
confidence: 99%
“…Tools to advance genetic interrogation of the killifish have been developed, including a sequenced genome (Reichwald et al, 2015; Valenzano et al, 2015) and Tol2 transgenesis (Allard et al, 2013; Hartmann and Englert, 2012; Valenzano et al, 2011), as well as CRISPR/Cas9-mediated knock-out (Harel et al, 2015) and CRISPR/Cas13-mediated knock-down (Kushawah et al, 2020). This genetic toolkit has enabled discoveries about the mechanisms of aging (Astre et al, 2022a; Bradshaw et al, 2022; Chen et al, 2022; Harel et al, 2022; Louka et al, 2022; Matsui et al, 2019; Smith et al, 2017; Van Houcke et al, 2021b), regeneration (Vanhunsel et al, 2022a; Vanhunsel et al, 2021; Vanhunsel et al, 2022b; Wang et al, 2020), evolution (Cui et al, 2019; Sahm et al, 2017; Singh et al, 2021; Willemsen et al, 2020), development (Abitua et al, 2021; Dolfi et al, 2019), and ‘suspended animation’ (Hu et al, 2020; Singh et al, 2021).…”
Section: Main Textmentioning
confidence: 99%
“…Interestingly, killifish appear to pay a price for their fast growth and aging. In contrast to zebrafish –that maintain their neuroreparative ability albeit regenerate less efficiently at old age [ 2 4 ] –, killifish completely lose their regeneration capacity at old age and are unable to fully recover from CNS injury [ 5 , 6 ]. Using an optic nerve crush injury model in killifish of different ages, we indeed revealed that, in contrast to young fish, aged animals do not regain vision following damage.…”
mentioning
confidence: 99%
“…Using an optic nerve crush injury model in killifish of different ages, we indeed revealed that, in contrast to young fish, aged animals do not regain vision following damage. An inadequate intrinsic capacity of aged retinal ganglion cells (RGCs) to revert to a “regenerative state” as well as a growth-inhibiting neuron-extrinsic environment seem to contribute to this impairment [ 6 ], similar to what has been described for (young) adult mammals. We postulate that age-associated changes within neurons and their glial environment –already manifesting before damage occurs– negatively affect the regeneration potential of the killifish CNS, which then leads to a mammalian-like regenerative response upon injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation